Impact of Internal Audit Unit in enhencing efficient use of public resources: A case study of Ministry of Finance – Zanzibar (MOF). - Rubea, Hamad O. (Mzumbe university, 2024)
A dissertation Submitted to Mzumbe University as a partial fulfillment of the requirement for the award of Master’s Degree of Accounting and Finance (MSc.A&F) of Mzumbe University.